A DETERMINATION OF THE FLUX DENSITY IN CORE OF DISTRIBUTION TRANSFORMERS, WHAT BUILT WITH THE COMMON USING OF GRAIN AND NON GRAIN ORIENTED MAGNETIC STEELS - Pentegov, I. V.; Rymar, S. V.; Levin, M. I.; Lavreniuk, A. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2015)
Purpose. The development of calculation method to determinate the flux densities in different parts of the magnetic cores of distribution transformers, what built from different types magnetic steel (mixed core). Methodology. The method is based on the scientific positions of Theoretical Electrical Engineering – the theory of the electromagnetic field in nonlinear mediums to determine the distribution of magnetic flux in mixed core of transformer, what are using different types of steel what have the different magnetic properties. Results. The developed method gives possible to make calculation of the flux density and influence of skin effect in different parts of the magnetic cores of distribution transformer, where are used mix of grain oriented (GO) and non grain oriented (NGO) steels. Was determinate the general basic conditions for the calculation of flux density in the laminations from grain and non grain oriented steels of the magnetic core: the strength of magnetic field for the laminations of particular part of mixed core is the same; the sum of the magnetic fluxes in GO and NGO steels in particular part of mixed core is equal with the designed magnetic flux in this part of mixed core. Discover, the magnetic flux in mixed core of the transformer has specific distribution between magnetic steels. The flux density is higher in laminations from GO steel and smaller in laminations from the NGO steel. That is happened because for magnetic flux is easier pass through laminations from GO steel, what has better magnetic conductance than laminations from NGO steel. Originality. The common using of different types of magnetic steels in cores for distribution transformers gives possibility to make design of transformer with low level of no load losses, high efficiency and with optimal cost. Practical value. The determination of the flux density in different parts of magnetic core with GO and NGO steels gives possibility make accurate calculation of no load losses and magnetizing current of the transformer.